Diseño de una antena microstrip con polarización circular para el Laboratorio de Antenas - Chimborazo Pujos, Liliana Elizabeth (2017)
In the present project, the design of a microstrip antenna with circular polarization for the laboratory of antennas is presented for which it was investigated first on the antennas and their characteristics, also was investigated on the Microstrip antennas, characteristics, types of geometries, structure of antenna, radiation parameters, types of power for circular polarization and in this way, choose the technique to achieve the circular polarization to a band of 2.4 GHz. In addition, this will review the functionality and characteristics of the software of simulation HFSS to make the design and simulation of a Microstrip antenna with circular polarization. Once the technique for the design was selected, the Microstrip antenna with circular polarization was designed to a band of 2.4 GHz establishing the parameters of an antenna in order to obtain a better design. Finally, we proceed with the simulation of the antenna designed by the microstrip line feed technique to obtain the radiation parameters: bandwidth, gain, efficiency and directivity. With the results obtained in the simulations of each design, a comparative analysis of a patch-type Microstrip antenna with circular polarization with a patch antenna with linear polarization.